THE USE OF MULTIMEDIA AND INTERACTIVE TECHNOLOGIES IN TEACHING PHYSICAL PHENOMENA BASED ON ENVIRONMENTAL AND SOCIO-ECONOMIC PROBLEMS IN THE TERRITORY OF KARAKALPAKSTAN - Abdijaliev, Sultanbek Kallibekovich; Omarova, Zamira Allamjarovna (SCIENCE and SOCIETY, 2026)
The article examines the didactic potential of using multimedia and interactive technologies in teaching physical phenomena based on environmental and socio-economic problems in the Republic of Karakalpakstan. It connects local environmental processes in the Aral Sea region with physics topics such as heat transfer, evaporation, diffusion, aerodynamics, radiation and energy transformation. The article does not present empirical experimental data; it focuses on the analysis of scientific and methodological literature, lesson design based on the local ecological context, and theoretical justification of expected pedagogical outcomes.